Iron therapy in hand eczema: A new approach for management - Ashimav Deb Sharma (Wolters Kluwer Medknow Publications, 2011)
It is observed that adequate iron intake and status can limit nickel absorption from the diet in the human body. Chronic vesicular hand eczema (CVHE) due to nickel sensitivity is a common dermatological condition where the dietary nickel acts as a provocating factor. Such patients are usually treated with low nickel diet (LND). The present study was conducted to observe the result of addition of oral iron with LND in the treatment of CVHE in patients due to nickel sensitivity. 23 patients with CVHE due to nickel sensitivity were taken for this study. Study group (12 patients) were advised LND with oral iron for a period of 12 weeks. Control group (11 patients) were advised LND alone for a period of 12 weeks. Fast improvement noted in the skin lesions of the study group patients; 10 (83.33%) patients had complete clearance of their hand eczemas at the end of 12 weeks. There were significant reductions in the blood level of nickel in those patients. Moderate improvement noted in the skin lesions of the control group patients; 5 (45.45%) patients showed complete clearance of hand eczema at the end of 12 weeks. This study showed that oral iron helped to reduce nickel absorption from the diet. The study also showed that combination of LND and oral iron can bring a faster reduction in the severity of clinical symptoms of CVHE in a nickel sensitive individual.